The King James Version Then and Now - Stine, Philip C. (Review and expositor, 2011)
For four hundred years, the King James Bible has been the principal Bible for millions of English-speaking Christians. Vocabulary and spelling have changed so that readers frequently misunderstand this Bible and find it difficult to read. Yet the language still finds its way into our daily speech and public discourse.The translation was a major influence on the standardization of the English language precisely because the translators were not attempting to create significant literature. Their aim was to produce a Bible that a largely illiterate audience could understand when it was read aloud.Its origins are found in the history and politics of sixteenth- and seventeenth-century England. When the English church broke with Rome, English Bibles were needed to confirm that rupture. However, the struggles first between Roman Catholics and Protestants, and then between the establishment Anglicans and Puritans, led to the situation by 1600 where the Geneva Bible was favored by the Puritans, but the Bible authorized for use in all the churches was the Bishops' Bible. When James I came to the English throne in 1603, the Puritans asked for more reform and authorization of the Geneva Bible. James ordered instead a new translation, and established a process and set of principles to ensure it was free of Calvinist doctrine and would support the monarchy and the established church. The Bible included the Apocrypha, which was normally included in printings until 1826.The Bible was published in 1611 in two versions. It is not known which was first. Different printers introduced numerous misprints and corrections over the years. Even today there are several different versions of the King James Bible published in America. There is no such thing as an original, flawless King James Bible.